Grass Root Constrictions in Implementation of MNREGA in West Bengal - Shubhadeep Roy , Baldeo Singh , R. N. Padaria; Neeraj Singh (Indian Journal of Extension Education, 2014)
The study was conducted in two districts, Burdwan and South Dinajpur of West Bengal with 200 MNREGAbeneficiaries and the MNREGAfunctionaries of block and village panchayat level as respondents to identify the major constrictions in the implementation of MNREGAat the grass root level. The major constrictions in the implementation as perceived by the beneficiaries were: incomplete list of adults in each household, delay in receiving job cards, wrong date or no date recorded on the work application, selection of a low priority or inappropriate work, favoring or discriminating against people in allocation of work, late payment of wages and various aspects of the programme carried out without people’s involvement. The major constrictions as perceived by the MNREGA functionaries were shortage of manpower, huge paper work and long bureaucratic structure, financial inclusion in MNREGA, problem of power cut and morality of the people.